GENETIC DIVERSITY ANALYSIS IN PALMYRAH PALMS USING RAPD MARKERS - DIDI CHINNU RAJU; J.V REJI (International Journal of Pharma and Bio Sciences, 2015)
Palmyrah palms (Borassus flabellifer), woody monocotyledons of the family Arecaceae is a common multipurpose tree of Tamilnadu state with great utility. 16 accessions from Tamil Nadu State of palmyrah were investigated for their genetic relationship using Random Amplified Polymorphic DNA markers. A total of 20 primersused for screening out of which 15 RAPD primers show consistency in giving polymorphic bands was selected for analysis. The fifteen primers produced a total of 112 reproducible bands and out of these amplified fragments, 82 (73.2%) were found to be polymorphic. The number of products produced by these arbitrary 10-mer primers was found to range from 1 to 14 with a maximum (14) by the primer UBC- 06 and primer UBC-15 produced the minimum (1) number of amplicons. The similarity matrix constructed using the WINDIST software showed the similarity index ranges from 0.60 to 0.93 with mean value 0.79 thereby suggesting high levels of genetic variability among the male and female plants of this species. Cluster analysis based on Jaccard’s similarity coefficient using UPGMA grouped all male and female accessions separately into two major clusters. The relatively high polymorphism suggests a moderately high genetic diversity of palmyrah populations from which the present accessions have been derived and maintained over years.